High bio-content polyurethane hot melt adhesive composition
A high bio-content polyurethane hot melt adhesive composition, using bio-based polyester polyols and polyisocyanate, addresses the lack of impact toughness in existing adhesives, achieving superior bonding strength and impact resistance for electronic device applications.
Patent Information
- Application Number
- JP2024542014
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-01-24
AI Technical Summary
Existing polyurethane hot melt adhesives lack sufficient impact toughness and cannot simultaneously achieve high initial cross tensile strength and excellent impact resistance, particularly in the construction of electronic devices, and there is a need for increased bio-content without compromising performance.
A high bio-content polyurethane hot melt adhesive composition comprising bio-based solid crystalline and amorphous polyester polyols, polyisocyanate, and optional additives, prepared by reacting polyester polyols and polyisocyanate under controlled conditions to form a polyurethane prepolymer, which includes more than 50% bio-based materials.
The composition exhibits excellent bonding strength and good impact resistance, surpassing prior art adhesives in terms of bio-content and performance metrics such as DuPont impact energy, cross tensile strength, and lap shear strength.
Smart Images

Figure 2025502270000001 
Figure 2025502270000002 
Figure 2025502270000003
Abstract
Description
[Technical field]
[0001] Technical Field The present invention relates to a high bio-content polyurethane hot melt adhesive composition, a process for preparing said high bio-content polyurethane hot melt adhesive composition, electronic devices obtained with said high bio-content polyurethane hot melt composition, and the use of said high bio-content polyurethane hot melt composition in the manufacture of electronic devices. [Background technology]
[0002] Background technology Polyurethane hot melt adhesives have a long history and are widely used. In industrial applications, polyurethane hot melt adhesives are solid at room temperature and when heated to a moderate temperature, they melt into a viscous liquid that can be applied to the substrates to be bonded. The molten adhesive composition then cools and solidifies to form an initial bond to the substrates. It can further react with moisture to form crosslinked structures that can achieve high final strength. Such adhesives consist of a polyol component and an isocyanate component with a functionality of 2 or higher. In many applications, these adhesives are preferred because the adhesive bonds produced with them have superior bond strength, flexibility, and resistance to impact and fatigue compared to other adhesives.
[0003] Although polyurethane hot melt adhesives provide very good adhesive bonds in many fields of use, adhesives of this type known to date are not suitable for adhesive bonding of structures of plastic or metal workpieces, since they do not have sufficient impact toughness, and in particular in the manufacture of electronic devices, where fast curing is required, it is difficult for the cured adhesive to simultaneously achieve high initial cross tensile strength and good impact resistance.
[0004] Polyurethane hot melt adhesives consist of a polyol component and a polyisocyanate with a functionality of 2 or higher. Typically, polyols based on petrochemical feedstocks are used to synthesize these polyurethane compositions. Increasing customer demands for sustainably derived materials and the growing drive to introduce more sustainable practices in industry are leading to the need to increase the bio-based content in adhesive products. The challenge arises that the performance of the adhesive must not be adversely affected by the increased bio-content and the limited toolbox of bio-based raw materials.
[0005] In view of the above, it is desirable to provide a high bio-content polyurethane hot melt adhesive composition, wherein the adhesive composition contains more than 50 wt. % bio-based materials, based on the total weight of the adhesive composition; at the same time, such high bio-content polyurethane hot melt adhesive composition exhibits excellent bond strength and good impact resistance. Summary of the Invention
[0006] Summary of the Invention The primary objective of the present invention is to: a) at least one bio-based solid crystalline polyester polyol; b) at least one solid bio-based amorphous polyester polyol, and / or at least one liquid bio-based amorphous polyester; and c) at least one polyisocyanate; in the presence of a catalyst, wherein the adhesive composition comprises more than 50 wt. % of bio-based materials, based on the total weight of the adhesive composition.
[0007] Another object of the present invention is a process for preparing a high bio-content polyurethane hot melt adhesive composition according to any of claims 1 to 12, comprising: (i) adding all of said polyester polyol and optionally (meth)acrylic resin and melt mixing them until homogeneous and free of moisture; (ii) adding at least one polyisocyanate and mixing the resulting mixture under vacuum at 80° C. to 120° C. until the reaction is complete; and (iii) adding a catalyst and, optionally, additives, and stirring the mixture at 80°C to 120°C until homogenous. The object of the present invention is to provide a method comprising the steps of:
[0008] Yet another object of the present invention is to provide electronic devices obtained with the high bio-content polyurethane hot melt composition according to the present invention.
[0009] Yet another object of the present invention is to provide the use of the high bio-content polyurethane hot melt composition according to the present invention in the manufacture of electronic equipment.
[0010] Compared to polyurethane hot melt adhesive compositions in the prior art, the high bio-content polyurethane hot melt adhesive composition according to the present invention contains more than 50 wt. % bio-based materials, based on the total weight of the adhesive composition, and at the same time exhibits excellent bond strength and good impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Detailed Description of the Invention It will be understood by those skilled in the art that the present invention is a description of exemplary embodiments only and is not intended to limit the broader aspects of the present invention. Each embodiment so described may be combined with any other embodiment or any other embodiments unless expressly indicated to be incompatible. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or any other features indicated as being preferred or advantageous.
[0012] Unless otherwise specified, in the context of the present invention, the terms used are to be construed in accordance with the following definitions.
[0013] As used herein, unless otherwise specified, the terms "a," "an," and "the" include singular and plural references.
[0014] As used herein, the terms "comprising" and "comprises" are synonymous with "including," "includes," or "containing," and "contains," and are inclusive or open-ended, and do not exclude additional, unrecited items, elements, or manufacturing steps.
[0015] The terms "at least one" or "one or more" as used herein to define a component refer to the type of component and not the absolute number of molecules. For example, "one or more polyols" refers to one type of polyol or a mixture of multiple different polyols.
[0016] As used herein, the term "amorphous" means having no melting transition as measured using differential scanning calorimetry (DSC).
[0017] As used herein, the term "crystalline" means having a melting transition as measured using differential scanning calorimetry (DSC).
[0018] As used herein, the term "room temperature" refers to a temperature of about 20°C to about 25°C, preferably about 25°C.
[0019] As used herein, the term "bio-based" refers to materials that are derived from renewable resources (and are not petroleum-based). However, it should be noted that the term does not refer to the manufacturing process of the material, only the resource from which the material is derived. For example, ASTM D 6866 is used to determine the bio-based content of a material.
[0020] Unless otherwise specified, the recitation of numerical endpoints includes not only the recited endpoints but also all numerical values and fractions subsumed within each range.
[0021] All documents cited herein are incorporated by reference in their entirety.
[0022] Molecular weight means number average molecular weight (Mn) unless otherwise specified. All molecular weight data refer to values obtained by gel permeation chromatography (GPC), e.g. DIN 55672, unless otherwise specified.
[0023] In this context, the glass transition temperature (Tg) or melting point of a particular polymer is determined using DSC according to DIN 53765.
[0024] The softening points referred to in this specification are determined by using the ring and ball method according to DIN ISO 4625.
[0025] Unless otherwise defined, all terms used herein, including technical and scientific terms, have the meaning commonly understood by one of ordinary skill in the art to which this invention belongs.
[0026] In one aspect, the present disclosure generally relates to a method for producing a method for manufacturing a semiconductor device comprising: a) at least one bio-based solid crystalline polyester polyol; b) at least one solid bio-based amorphous polyester polyol, and / or at least one liquid bio-based amorphous polyester; and c) at least one polyisocyanate; 1. A high bio-content polyurethane hot melt adhesive composition comprising at least one polyurethane prepolymer obtained by reaction in the presence of a catalyst of High bio-content polyurethane hot melt adhesive compositions are directed to such compositions.
[0027] Polyurethane Prepolymer According to the present invention, the high bio-content polyurethane hot melt adhesive composition comprises at least one polyurethane prepolymer obtained by reaction in the presence of a catalyst of: a) at least one solid crystalline bio-based polyester polyol; b) at least one solid amorphous bio-based polyester polyol, and / or at least one liquid amorphous bio-based polyester; and c) at least one polyisocyanate.
[0028] In some embodiments, the polyurethane prepolymer has a number average molecular weight (Mn) of about 5,000 to about 30,000 g / mol, preferably about 8,000 to about 20,000 g / mol.
[0029] a) Bio-based solid crystalline polyester polyols According to the present invention, the bio-based solid crystalline polyester polyol can be derived from a reaction mixture comprising at least one polyacid or its derivative and at least one polyol. Preferably, the derivative of the polyacid is a carboxylic acid anhydride and / or ester of the polyacid. More preferably, the polyacid is a diacid, which is preferably selected from the group consisting of succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer fatty acid, 2,5-furandicarboxylic acid, adipic acid, and combinations thereof. In a preferred embodiment of the present invention, the polyol is a diol, which is preferably selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, isosorbide, and combinations thereof. Most preferably, the bio-based solid crystalline polyester polyol is derived from a reaction mixture comprising one long chain diacid with an even number of carbon atoms and one diol with an even number of carbon atoms.
[0030] In a preferred embodiment of the present invention, the bio-based solid crystalline polyester polyol has a melting point of about 10 to about 110° C., preferably about 30 to about 90° C., more preferably about 45 to about 80° C. In another preferred embodiment of the present invention, the bio-based solid crystalline polyester polyol has a number average molecular weight of more than about 1000 g / mol, preferably about 2000 to about 8000 g / mol, more preferably about 3700 to about 6500 g / mol.
[0031] Suitable commercially available bio-based crystalline polyester polyols are sold under the trade names Dynacoll Terra 7750 (Evonik), Bio-Hoopol 11003, Bio-Hoopol 11520 or Bio-Hoopol 12930 (Synthesia).
[0032] In a preferred embodiment of the present invention, the bio-based solid crystalline polyester polyol is present in an amount of from about 10 to about 40 weight percent, preferably from about 15 to about 35 weight percent, based on the total weight of the adhesive composition.
[0033] b) Bio-based solid amorphous polyester polyols and / or bio-based liquid amorphous polyester polyols According to the present invention, the bio-based solid amorphous polyester polyol is derived from a reaction mixture comprising at least one hexitol anhydride and at least one multifunctional carboxylic acid. Preferably, the bio-based solid amorphous polyester polyol is derived from a reaction mixture comprising at least one hexitol anhydride and at least one multifunctional carboxylic acid. More preferably, the bio-based solid amorphous polyester polyol is derived from a reaction mixture comprising isosorbide and at least one multifunctional carboxylic acid selected from the group consisting of adipic acid, succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, furandicarboxylic acid, isophthalic acid, terephthalic acid, orthophthalic acid, dimerized fatty acid, trimerized fatty acid, and mixtures thereof. Most preferably, the bio-based solid amorphous polyester polyol is derived from a reaction mixture comprising isosorbide, succinic acid, and dimer fatty acid.
[0034] Hexitol anhydrides are obtained by dehydration of hexitols such as sorbitol (glucitol), mannitol, and iditol, which are produced by reducing the carbonyl group of hexoses such as glucose, mannose, and idose, which are usually obtained from several biological sources such as wheat, corn, and cellulose.
[0035] Double dehydration gives dianhydrohexitols. Usually, the anhydrous hexitols are dianhydrohexitols, such as dianhydromannitol, dianhydrosorbitol, dianhydroiditol and mixtures thereof. Preferably, the dianhydrohexitols are dianhydrosorbitols, such as isosorbide, isomannide and isoidide, more particularly isosorbide. There are several companies that specialize in the production of isosorbide, isomannide and isoidide.
[0036] Preferably, the amount of the at least one hexitol anhydride is from about 20 mole % to about 60 mole %, based on the total moles of the polyester polyol reactants.
[0037] In addition to the hexitol anhydride, the polyester polyol reactants may optionally include at least one polyol other than the hexitol anhydride for reaction with the polyfunctional carboxylic acid.
[0038] Examples of such polyols include monoethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol (including R-, S- and racemic forms), 1,4-butanediol, 1,4-pentanediol, 3-methylpentane-1,5-diol, neopentyl glycol (2,2-dimethyl-1,3-propanediol), 1,5-pentanediol, 1,6-hexanediol, 1,8-octane glycol, cyclohexanedimethanol, 2-methylpropane-1,3-diol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, polypropylene glycol, dibutylene glycol and polybutylene glycol.
[0039] Preferably, the polyols other than hexitol anhydrides are completely bio-based. Examples of such polyols include, but are not limited to, glycerol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol (including R-, S- and racemic forms), 1,4-butanediol, 1,4-pentanediol, 1,5-pentanediol, ethylene glycol, diethylene glycol and triethylene glycol. These polyols may be used alone or in combination.
[0040] In one embodiment, the polyester polyol reactants include at least one polyol other than a hexitol anhydride, and when present, the amount of polyol other than a hexitol anhydride is from about 1 mol % to about 35 mol %, based on the total moles of the polyester polyol reactants.
[0041] In another embodiment, the polyester polyol reactants include only hexitol anhydrides as the polyol source for the preparation of polyester polyols according to the invention.
[0042] The polyester polyols can be prepared according to the present invention by polycondensation of hexitol anhydrides and optionally at least one polyol other than hexitol anhydrides with a substoichiometric amount of a polyfunctional carboxylic acid in the presence of a catalyst.Preferably, the polyfunctional carboxylic acid has 2 to 36 carbon atoms, such as dicarboxylic acids and / or tricarboxylic acids, or reactive derivatives thereof, such as carboxylic acid anhydrides, chlorides and esters.
[0043] Examples of dicarboxylic acids include adipic acid, succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, furandicarboxylic acid, isophthalic acid, terephthalic acid, orthophthalic acid, dimerized fatty acid, trimerized fatty acid, etc. These dicarboxylic acids are used alone or in combination. Examples of carboxylic acid anhydrides include adipic acid anhydride, succinic acid anhydride, etc. These dicarboxylic acid anhydrides are used alone or in combination. In one embodiment, the polyfunctional carboxylic acid is selected from succinic acid, azelaic acid, sebacic acid, dimerized fatty acid, trimerized fatty acid, and mixtures thereof.
[0044] Dimerized fatty acids are the dimerization products of mono- or polyunsaturated acids and / or their esters. Preferred dimerized fatty acids are dimers of C10- to C36-, more preferably C12- to C24-, especially C14- to C22-alkyl chains. Suitable dimerized fatty acids include the dimerization products of oleic acid, linoleic acid, linolenic acid, palmitoleic acid and elaidic acid. Dimerization products of unsaturated fatty acid mixtures obtained by hydrolysis of natural fats and oils, such as sunflower oil, soybean oil, olive oil, rapeseed oil, cottonseed oil and tall oil, may also be used. Examples of dimerized (dimer) fatty acids are Pripol 1019, 1013, 1017, 1006, available from Croda.
[0045] According to the present invention, the amount of the at least one multifunctional carboxylic acid is about 50 mole % or less, preferably about 40 to about 50 mole %, based on the total moles of polyester polyol reactants.
[0046] The polycondensation of the hexitol anhydride and optionally the polyol with the polyfunctional carboxylic acid is carried out in the presence of at least one catalyst. The catalyst is a non-metallic inorganic acidic catalyst selected from non-metallic inorganic acidic compounds having a phosphorus atom in the oxidation state of +1, non-metallic inorganic acidic compounds having a phosphorus atom in the oxidation state of +3, and mixtures thereof. In a preferred embodiment, the at least one non-metallic inorganic acidic catalyst is selected from phosphinic acids, phosphonic acids, and mixtures thereof. In a further preferred embodiment, the non-metallic inorganic acidic catalyst is phosphinic acid.
[0047] In a preferred embodiment of the present invention, the bio-based solid amorphous polyester polyol has a glass transition temperature (Tg) of about 5 to about 80° C., preferably about 10 to about 50° C., more preferably about 15 to about 45° C. In another preferred embodiment of the present invention, the bio-based solid amorphous polyester polyol has a number average molecular weight of more than about 1000 g / mol, preferably about 1700 to about 5500 g / mol, more preferably about 2000 to about 3000 g / mol.
[0048] Suitable commercially available bio-based solid amorphous polyester polyols are sold under the trade name Dynacoll Terra 7540 (Evonik), which are partially bio-based.
[0049] According to the present invention, the bio-based liquid amorphous polyester polyol can be derived from a reaction mixture comprising at least one polyol and at least one polyacid or its derivative. Preferably, the derivative of the polyacid is a carboxylic anhydride and / or ester of the polyacid. In a preferred embodiment of the present invention, the polyol is selected from the group consisting of 1,2-propanediol, 1,3-butanediol (including R-, S- and racemic forms), 1,4-pentanediol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol and polypropylene glycol, or mixtures thereof. In another preferred embodiment of the present invention, the polyacid is selected from the group consisting of succinic acid, azelaic acid, sebacic acid, dodecanedioic acid and dimerized fatty acid, or mixtures thereof. Most preferably, the bio-based liquid crystalline polyester polyol is derived from a reaction mixture comprising azelaic acid and diethylene glycol.
[0050] In a preferred embodiment of the present invention, the bio-based liquid amorphous polyester polyol has a glass transition temperature of less than about 0° C., preferably about −75 to about −15° C., more preferably about −65 to about −20° C. In another preferred embodiment of the present invention, the bio-based liquid amorphous polyester polyol has a number average molecular weight of more than about 1000 g / mol, preferably about 1500 to about 5500 g / mol, more preferably about 2000 to about 3200 g / mol.
[0051] Suitable commercially available bio-based liquid amorphous polyester polyols are sold under the trade names Dynacoll Terra 7640 (Evonik), Priplast 3238 (Croda), Bio-Hoopol 11034, Bio-Hoopol 13033, Bio-Hoopol 13034 (Synthesia).
[0052] In a preferred embodiment of the present invention, the total content of the bio-based solid amorphous polyester polyol and / or the bio-based liquid amorphous polyester polyol is about 15 to about 70% by weight, preferably about 20 to about 50% by weight, based on the total weight of the adhesive composition.
[0053] In the present invention, the solid crystalline bio-based polyester polyol, the solid amorphous bio-based polyester polyol and / or the liquid amorphous bio-based polyester polyol may be partially or completely bio-based.
[0054] In one embodiment of the present invention, the high bio-content polyurethane hot melt adhesive composition according to the present invention may further comprise at least one non-bio-based solid crystalline polyester polyol and / or at least one non-bio-based liquid amorphous polyester polyol, so long as the adhesive composition comprises more than 50 wt.% bio-based material, based on the total weight of the adhesive composition.
[0055] In another preferred embodiment of the present invention, the high bio-content polyurethane hot melt adhesive composition comprises at least one solid crystalline bio-based polyester polyol, at least one solid amorphous bio-based polyester polyol, and at least one liquid amorphous bio-based polyester.
[0056] c) Polyisocyanate In the present invention, the polyisocyanate can be any suitable isocyanate having at least two isocyanate groups in one molecule, including, for example, aliphatic, cycloaliphatic, cycloaliphatic, arylalkyl, and aromatic isocyanates, and combinations thereof.
[0057] Preferred polyisocyanates are 4,4-diphenylmethane diisocyanate (MDI), hydrogenated MDI (H12MDI), partially hydrogenated MDI (H6MDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), 4,4-diphenyldimethylmethane diisocyanate, dialkylene diphenylmethane diisocyanate, tetraalkylene diphenylmethane diisocyanate, 4,4-diphenyl isocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isomers of toluylene diisocyanate (TDI), 1-methyl-2,4-diisocyanatocyclohexane, 1,6-diisocyanato-2,2,4-trimethylhexane, 1,6-diisocyanato-2,4,4-trimethylhexane, 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), tetraisocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), Methoxybutane-1,4-diisocyanate, Naphthalene-1,5-diisocyanate (NDI), Butane-1,4-diisocyanate, Hexane-1,6-diisocyanate (HDI), Dicyclohexylmethane diisocyanate, 2,2,4-trimethylhexane-2,3,3-trimethylhexamethylene diisocyanate, Cyclohexane-1,4-diisocyanate, Ethylene diisocyanate, Methylenetriphenyl triisocyanate The polyisocyanate may be selected from the group consisting of bisisocyanatoethyl ester (MIT), phthalic acid bisisocyanatoethyl ester, trimethylhexamethylene diisocyanate, 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, and dimer fatty acid diisocyanates, lysine ester diisocyanates, 4,4-dicyclohexylmethane diisocyanate, 1,3-cyclohexane or 1,4-cyclohexane diisocyanate, and combinations thereof. The most preferred polyisocyanates are 4,4-diphenylmethane diisocyanate (MDI) and its isomers, chain extended MDI, and combinations thereof.
[0058] Useful commercially available polyisocyanates include DESMODUR 44 C FUSED, Desmodur 0118 I, and Desmodur 44M from Covestro, Vannate MDI 100F from Wanhua Chemicals, Supresec 1809 from HUNTSMAN.
[0059] In a preferred embodiment of the invention, the polyisocyanate is present in an amount of from about 10 to about 25 weight percent, preferably from about 15 to about 22 weight percent, based on the total weight of the adhesive composition.
[0060] In one embodiment of the present invention, the high bio-content polyurethane hot melt adhesive composition may further comprise at least one polyether polyol and / or at least one (meth)acrylic resin.
[0061] Polyether polyol The polyether polyols used in the present invention are well known to those skilled in the art. These polyether polyols are obtained by copolymerizing at least one compound, such as ethylene oxide, propylene oxide, butylene oxide, tetrahydrofuran, and at least one compound having at least two active hydrogen atoms in average in one molecule, such as the above polyhydric alcohols, including ethylene glycol, propylene glycol, dipropylene glycol, glycerol, and combinations thereof. Other suitable polyhydric compounds include sucrose, ethylenediamine, propylenediamine, triethanolamine, 1,2-propanedithiol, and combinations thereof.
[0062] Preferred polyether polyols may be selected from polytetramethylene ether glycol, poly(oxypropylene) glycol, polyethylene oxide, polybutylene oxide, and ethylene oxide end-capped versions of any of the foregoing, and combinations thereof. Most preferred polyether polyols are polytetramethylene ether glycol, poly(oxypropylene) glycol, ethylene oxide end-capped poly(oxypropylene) glycol, and combinations thereof.
[0063] In the present invention, the polyether polyols may be bio-based or non-bio-based.
[0064] In a preferred embodiment, the polyether polyol has a number average molecular weight (Mn) of about 200 to about 8000 g / mol, preferably about 400 to about 4000 g / mol, and more preferably about 400 to about 2000 g / mol.
[0065] Examples of commercially available polyether polyols useful in the present invention include, but are not limited to, bio-based Voranol 2104, 2110, 2120 and 2140 from Dow Chemical Company, and Velvetol H2000 and H1000 from Weylchem.
[0066] Particularly preferably, the polyether polyol is present in an amount of from about 2% to about 30% by weight, and more preferably from about 5% to about 15% by weight, based on the total weight of the adhesive composition.
[0067] (Meth)acrylic resin The (meth)acrylic resins used in the present invention may be linear or branched, may consist of copolymerized alkyl-, acid- and tertiary amine-functional (meth)acrylic monomers, and may contain other functional groups that do not react rapidly with isocyanate functionality. Branching of the (meth)acrylic resins can be induced by copolymerizing polyfunctional comonomers and / or by using polyfunctional chain transfer agents and / or polyfunctional initiators.
[0068] Suitable comonomers for use in forming the (meth)acrylic resins of the present invention include C1-C12 esters of methacrylic and acrylic acids, including but not limited to methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-hexyl methacrylate, n-octyl methacrylate, 2-ethylhexyl methacrylate, dodecyl (lauryl) methacrylate or similar acrylates. Mixtures of compatible (meth)acrylate monomers may also be used. Methacrylic and acrylic comonomers based on esters of methacrylic and acrylic acids with poly(ethylene glycol) and / or poly(propylene glycol) and / or glycol ethers may also be used. Other additional vinyl comonomers that may be used include vinyl esters (e.g., vinyl acetate and vinyl propionate); vinyl ethers; crotonic, maleic, fumaric and itaconic acid esters; styrene; alkyl styrenes; acrylonitrile; butadiene; and the like, and their comonomers. The particular monomer selected will depend primarily on the end use for which the adhesive is intended.
[0069] Suitable acid-functional comonomers for use in forming the (meth)acrylic resins of the present invention include, but are not limited to, methacrylic acid and acrylic acid.
[0070] Suitable hydroxyl-functionalized comonomers that can be used and incorporated to form the (meth)acrylic resins of the present invention include, but are not limited to, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and 2-hydroxybutyl methacrylate or similar acrylates.
[0071] Suitable amine-functionalized comonomers for use in forming the (meth)acrylic resins of the present invention include, but are not limited to, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, or similar acrylates.
[0072] (Meth)acrylic resins can be prepared by free radical polymerization, with the molecular weight (Mn) controlled by using chain transfer agents, such as catalytic chain transfer agents based on thiols or transition metal complexes, e.g., dodecyl mercaptan. Branched (meth)acrylic resins are produced by copolymerizing multifunctional monomers and / or using multifunctional chain transfer agents and / or using multifunctional initiators.
[0073] In a preferred embodiment, the (meth)acrylic resin has a number average molecular weight (Mn) of about 5,000 to about 100,000 g / mol, preferably about 5,000 to about 80,000 g / mol, and more preferably about 8,000 to about 50,000 g / mol.
[0074] Examples of commercially available (meth)acrylic resins useful in the present invention include, but are not limited to, Diinal MB-2595 and Elvacite 2013 available from Mitsui Chemicals, Inc.
[0075] According to the present invention, the content of the (meth)acrylic resin may be less than about 20% by weight, based on the total weight of the adhesive composition.
[0076] catalyst The catalysts used in the present invention are used to promote the reaction of polyester polys with polyisocyanates.
[0077] Suitable catalysts include, for example, strongly basic amides such as 2,3-dimethyl-3,4,5,6-tetrahydropyrimidine, tris-(dialkylaminoalkyl)-s-hexahydrotriazines such as tris-(N,N-dimethylaminopropyl)-s-hexahydrotriazine, or arylamines such as triethylamine, tributylamine, dimethylbenzylamine, N-ethyl-hexylmorpholine, N-methyl-hexylmorpholine, N-cyclohexyl- Morpholine, dimethylcyclohexylamine, dimorpholinodiethyl ether, 2-(dimethylaminoethoxy)-ethanol, 1,4-diazabicyclo[2,2,2]octane, 1-azabicyclo[3,3,0]octane, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylbutanediamine, N,N,N',N'-tetramethylhexane-1,6-diamine, pentamethyldiethylenetriamine, tetramethyldiamino These include common tertiary amines such as ethyl ether, bis-(dimethylaminopropyl)-urea, N,N'-dimethylpiperazine, 1,2-dimethylimidazole, di-(4-N,N-dimethylaminocyclohexyl)-methane, and organometallic compounds such as titanates, for example iron compounds such as iron(III) acetylacetonate, tin compounds such as tin(II) diacetate, tin(II) salts of organic carboxylic acids such as tin(II) dilaurate, or dialkyltin(IV) salts of organic carboxylic acids such as dibutyltin(IV) diacetate, dibutyltin(IV) dilaurate, dibutyltin(IV) malate or dioctyltin(IV) diacetate, and dibutyltin(IV) dimercaptide or mixtures of two or more of the above catalysts, as well as synergistic combinations of strongly basic amines and organometallic compounds.
[0078] The catalyst is present in the adhesive composition in an amount of from about 0.05% to about 1% by weight, and preferably from about 0.05% to about 0.5% by weight, based on the total weight of the adhesive composition.
[0079] Additives Optionally, the high bio-content polyurethane hot melt adhesive composition may contain at least one additive, such as a leveling agent, an adhesion promoter, an antioxidant, a film former, or the like, that is commonly used in the art.
[0080] Examples of leveling agents include acrylate copolymers, which may be commercially available under the trade name Efka FL 3740 from BASF.
[0081] An example of an adhesion promoter includes gamma-mercaptopropyltrimethoxysilane, which may be commercially available under the trade name Silquest A 189 from Momentive Performance Materials.
[0082] Examples of antioxidants include phenolic types such as BHT (butylated hydroxytoluene), octadecyl-3,5-bis(1,1-dimethyl)-4-hydroxybenzenepropanoate, pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and pyrogallol; phosphites such as triphenyl phosphite, tris(nonylphenyl)phosphite; or thioesters such as dilauryl thiodipropionate, and combinations thereof. In particular, the antioxidant may be pentaerythritol tetrakis (3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), which may be commercially available under the trade name Evernox 10 from the Everspring company.
[0083] An example of a film-forming agent is 1-(P-toluenesulfonyl)imidazole (PTSI), which may be commercially available from the VanDeMark company.
[0084] When present, the additives may be present in an amount of from about 0.01% to about 2% by weight, preferably from about 0.05% to about 1% by weight, based on the total weight of the adhesive composition.
[0085] Compared to prior art polyurethane hot melt adhesive compositions, the high bio-content polyurethane hot melt adhesive composition of the present invention contains more than 50 wt. % bio-based materials, based on the total weight of the adhesive composition, while exhibiting excellent bond strength and good impact resistance.
[0086] Method for preparing high bio-content polyurethane hot melt adhesive composition The high bio-content polyurethane hot melt adhesive composition according to the present invention may be prepared by any method conventionally used in the art, so long as all components therein can be uniformly mixed. In particular, the high bio-content polyurethane hot melt adhesive composition according to the present invention comprises the following: (i) adding all of the polyester polyol and optionally the (meth)acrylic resin, melting and mixing until homogeneous and free of moisture; (ii) adding at least one polyisocyanate and mixing the resulting mixture under vacuum at 80° C. to 120° C. until the reaction is complete; and (iii) Add catalyst and optional additives and stir the mixture at 80°C to 120°C until homogenous. It may be prepared as follows.
[0087] The apparatus for preparing the high bio-content polyurethane hot melt adhesive composition according to the present invention may be any conventional apparatus in the art, examples of which include an automatic mortar, a Henschel mixer, a three-roll mill, a ball mill, a planetary stirrer and a bead mill, which are equipped with an agitator and a heater.
[0088] electronic equipment The present invention further provides an electronic device, preferably a handheld device assembly, obtainable with the high bio-content polyurethane hot melt adhesive composition according to the present invention.
[0089] The high bio-content polyurethane hot melt adhesive composition of the present invention can be applied to a substrate using any suitable application method including, for example, automated fine line application, jet application, slot die coating, roll coating, gravure coating, transfer coating, pattern coating, screen printing, spray coating, extrusion, air knife, trailing blade, brushing, dipping, filament coating with a doctor blade, offset gravure coating, rotogravure application, and combinations thereof. The high bio-content polyurethane hot melt adhesive composition can be applied as a continuous or discontinuous coating, in single or multiple layers, and combinations thereof.
[0090] use Finally, the present invention provides the use of the high bio-content polyurethane hot melt adhesive composition according to the present invention in the manufacture of electronic devices, preferably handheld device assemblies.
[0091] Suitable electronic devices include, but are not limited to, wearable electronic devices (e.g., watches and glasses), handheld electronic devices (e.g., phones (e.g., cell phones and smart phones), cameras, tablets, e-readers, monitors (e.g., monitors used in hospitals and by medical personnel, athletes and individuals), watches, calculators, mice, touchpads, joysticks), computers (e.g., desktop and laptop computers), computer monitors, televisions, media players, or other electronic components.
[0092] The present invention will be described in more detail through the following examples, which should not be construed as limiting the concept of the present invention. EXAMPLES
[0093] Working Example All parts and percentages are by weight unless otherwise stated.
[0094] raw material The following raw materials were used in the examples:
[0095] Polyol: Polyether polyols: Voranol 2110, a commercial product from Dow Plastics, number average molecular weight 1000 g / mol. Velvetol H2000, 100% bio-based polyol, commercially available from WeylChem, number average molecular weight 2000 g / mol. Velvetol H1000, 100% bio-based polyol, commercially available from WeylChem, number average molecular weight 1000 g / mol.
[0096] Polyester polyol: Solid crystalline polyester polyols: Dynacoll 7380, commercial product from Evonik Degussa, number average molecular weight 3500 g / mol. Dynacoll 7360, commercial product from Evonik Degussa, number average molecular weight 3500 g / mol. Dynacoll 7340, commercial product from Evonik Degussa, number average molecular weight 3500 g / mol. Dynacoll Terra 7750, 100% bio-based polyol, commercially available from Evonik Degussa, number average molecular weight 3500 g / mol. PES 2, a 100% biobased solid, crystalline, saturated copolyester with an acid number below 2 mg KOH / g and a hydroxyl number between 25 and 35 mg KOH / g. Bio-Hoopol 11003, 100% bio-based polyol, commercial product from Synthesia, number average molecular weight 2000 g / mol.
[0097] Solid amorphous polyester polyols: Dynacoll 7111, a commercial product from Evonik Degussa, with a number average molecular weight of 3500 g / mol, and a glass transition temperature of 20°C. PES 1, a 100% biobased solid, solid amorphous, saturated copolyester with an acid number below 5 mg KOH / g and a hydroxyl number between 55 and 65 mg KOH / g. Dynacoll Terra 7540, a 35% bio-based polyol, commercially available from Evonik Degussa, number average molecular weight 3500 g / mol.
[0098] Liquid amorphous polyester polyols: Stepanpol PDP 70, commercial product from Stepan, number average molecular weight 1600 g / mol. Priplast 3238, 100% bio-based polyol, commercially available from Croda, number average molecular weight 2000 g / mol. PES 3, a 100% bio-based liquid amorphous, saturated copolyester, with an acid number below 2 mg KOH / g and a hydroxyl number between 55 and 65 mg KOH / g.
[0099] Acrylate polymer: Dialal MB-2595, a solid methacrylate copolymer bead resin with a number average molecular weight of 8,000 g / mol (Tg: approximately 59 °C), commercially available from Mitsui Chemicals, Inc. Elvacite 2013, a solid methacrylate copolymer bead resin with a number average molecular weight of 34,000 g / mol (Tg: approximately 80 °C), commercially available from Mitsui Chemicals, Inc.
[0100] catalyst: 2,2'-Dimorpholinodiethyl ether (DMDEE)
[0101] Polyisocyanates: 4,4'-MDI: Commercially available product manufactured by Covestro under the trade name Desmodur 44C.
[0102] Adhesion promoter: Silquest A 189, gamma-mercaptopropyltrimethoxysilane, commercially available from Momentive Performance Materials.
[0103] Additives: Efka FL 3740, acrylate copolymer, commercially available from BASF. Evernox 10, pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), a commercial product from Everspring company. PTSI, toluenesulfonyl isocyanate, a commercial product from VanDeMark company.
[0104] Preparation of polyester polyols The following raw materials were used to prepare PES 1 to PES 3. Sebacic acid was obtained from Sigma Aldrich. Succinic acid was obtained from Sigma Aldrich. Isosorbide was obtained from Roquette under the trade name Polysorb PA. Azelaic acid was obtained from Croda. Diethylene glycol was obtained from Sigma Aldrich. Ethylene glycol was obtained from Sigma Aldrich. Dimeric fatty acids were obtained from Croda under the trade name Pripol. Phosphinic acids were obtained from Sigma Aldrich. PES 1, PES 2, and PES 3 were prepared according to the formulations in Table 1.
[0105] The polyacid and polyol were charged into a 1- or 5-liter four-neck flask equipped with a nitrogen sparge tube, thermocouple, overhead stirrer and distillation arm. The mixture was heated stepwise up to 220 °C under nitrogen flow. The complete reaction could take about 20 to 40 h depending on the reaction composition (monomers and catalyst). The catalyst was added selectively directly from the beginning or midway of the polycondensation reaction. The system pressure was then reduced stepwise to 10-300 mbar to achieve complete conversion. Once the acid number was below 3 mg KOH / g, the reaction was cooled. The polyester polyols were characterized by acid number (mg KOH / g), hydroxyl number (mg KOH / g), viscosity at specific temperatures (Pa·s) as well as Mn (g / mol) by GPC method. DSC measurements were performed to determine the Tg (°C) and melting point Tm (°C) of the final polyester polyols.
[0106] [Table 1]
[0107] Preparation of Polyurethane Hot Melt Adhesive Compositions The polyurethane hot melt adhesive compositions of Comparative Examples 1-5 (Comparative Examples 1-5) and Inventive Examples 1-7 (Examples 1-7) containing the components shown in the table below were prepared as follows: All polyols and acrylate polymers (if any) were added, melted and mixed under vacuum until homogenous and free of moisture. Next, 4,4-MDI was added and polymerization was allowed to proceed under vacuum at 100°C with mixing until the reaction was complete after 1 hour. Finally, catalysts, adhesion promoters, and additives were added and the resulting mixture was stirred at 100°C for 10 minutes. The resulting reactive hot melt adhesive was then placed in a container under a dry nitrogen headspace to prevent exposure to moisture.
[0108] Test Method viscosity: According to EN ISO2555 using a Brookfield Digital Viscometer RVT with a thermoset heating unit, spindle 27, at 110°C, 10 rpm.
[0109] The fixture strength was measured by cross tensile strength: The room temperature adhesive strength values of assembled parts (stainless steel or polycarbonate plastic) were measured after 6 minutes, 40 minutes, and 2 hours of curing using the following method: First, polycarbonate and stainless steel substrates with width 25.4mm and length 101.6mm were prepared. They were cleaned with ethanol and then dried before use. Then, two 127um gap spacers were placed on the stainless steel lap shear. Two lines of adhesive (25.4mm long) were applied parallel to the center of the prepared surface of the stainless steel lap shear specimen. The distance between each bead of adhesive and the edge of the lap shear was 8mm. After applying the adhesive, the second lap shear specimen was assembled vertically, making sure that the adhesive line was perpendicular to the second (top) lap shear. A 2KG weight block was placed on top of the lap shear specimen for 15 seconds. The samples were cured for the required time at 23°C and 50% relative humidity. Cross tensile strength and anchorage strength were measured on a Zwick at a crosshead speed of 2.0mm / min. The load at failure and the failure mode (adhesive or cohesive failure) are recorded.
[0110] The ultimate bond strength was measured based on lap shear strength: 24 hours after final curing, the adhesive strength values of the assembled parts (stainless steel and polycarbonate plastic) were measured by the following method: First, two polycarbonate substrates with a width of 25.4 mm and a length of 101.6 mm were prepared. They were cleaned with isopropanol and dried before use. Then, two 127 μm gap spacers were placed on the stainless steel lap shear. One line of adhesive (25.4 mm long) was applied parallel to the center of the prepared surface of the polycarbonate lap shear specimen. The distance between the bead adhesive and the edge of the lap shear was 6.3 mm. After applying the adhesive, the second lap shear specimen was assembled horizontally, making sure that the adhesive line was aligned with the second (top) lap shear. A 2KG weight block was placed on top of the lap shear specimen for 15 seconds. The samples were cured for the required time at 23°C and 50% relative humidity. Cross tensile strength and anchorage strength were measured on a Zwick at a crosshead speed of 10.0 mm / min. The load at failure and the failure mode (adhesive or cohesive failure) were recorded.
[0111] DuPont Impact Energy Test: The impact resistance of the cured adhesive compositions was evaluated by DuPont impact energy using a lap shear assembly.
[0112] First, a polycarbonate substrate with a width of 25.4 mm and a length of 101.6 mm, a polycarbonate substrate with a width of 25.4 mm and a length of 101.6 mm and a hole with a diameter of 10 mm in the center, and a polyethylene terephthalate (PET) film with a thickness of 0.12 mm and a hole with a diameter of 12 mm in the center were prepared. The PET film had tape on one side for adhering to the polycarbonate substrate to control the width and thickness of the adhesive layer. The substrate was washed with isopropanol and left at ambient conditions for several minutes to ensure that the surface was completely dry. The PET film was adhered to the polycarbonate substrate, ensuring that the location of the central hole of the PET film was aligned with the location of the central hole of the polycarbonate substrate. The diameter of the polycarbonate substrate was 2 mm larger than the PET film, forming a circular ring area with a width of 1 mm.
[0113] The adhesive composition was then applied onto the polycarbonate substrate within the circular ring area, and then another polycarbonate substrate was placed across the central hole of the polycarbonate substrate to form a 1 mm wide, 0.12 mm thick adhesive layer sandwiched between the overlapping area, i.e., the circular ring area. The samples were cured for the required time of 72 hours at 23°C and 50% relative humidity.
[0114] Sample test: A 50g weight was dropped onto the test specimen starting at a height of 2cm. If the polycarbonate substrate did not peel off from the polycarbonate substrate three times, the weight was raised to a height 2cm higher than the previous drop height. If the polycarbonate substrate did not peel off from the polycarbonate substrate using the 50g weight at a height of 50cm, the test was next performed using a 60g weight. DuPont impact energy was calculated using the following equation: E=m * g * h * 0.01 In the formula, E is the impact energy (mJ), m is the weight (g) when the substrates are peeled off, h is the height (cm) of the weight that comes off when the substrates are peeled off, and g is 9.8 m / s 2 It is.
[0115] [Table 2]
[0116] From Table 2, it can be seen that the polyurethane hot melt adhesive composition according to the present invention (Example 1) has a higher bio content and exhibits better DuPont impact energy, cross tensile strength (PC / SUS), and lap shear strength (PC / PC) compared to the prior art polyurethane hot melt adhesive compositions that do not contain a solid crystalline bio-based polyester polyol (Comparative Example 1), a liquid amorphous bio-based polyester polyol (Comparative Example 2), or both a solid amorphous bio-based polyester polyol and a liquid amorphous bio-based polyester polyol (Comparative Example 3).
[0117] [Table 3]
[0118] As can be seen from Table 3, compared to the prior art polyurethane hot melt adhesive composition not containing a bio-based solid crystalline polyester polyol (Comparative Example 4) or a bio-based liquid amorphous polyester polyol (Comparative Example 5), the polyurethane hot melt adhesive composition according to the present invention (Example 2) had a higher bio content and showed better DuPont impact energy, cross tensile strength (PC / SUS) and lap shear strength (PC / PC).
[0119] [Table 4] TIFF2025502270000005.tif56156
[0120] As can be seen from Table 4, among the polyurethane hot melt adhesive compositions according to the present invention, those containing bio-based polyether polyol, those containing petroleum-based crystalline polyester polyol, and those not containing (meth)acrylic resin all had a high bio content and showed extremely good DuPont impact energy, cross tensile strength (PC / SUS), and lap shear strength (PC / PC) within the protection range of the present invention.
[0121] While several preferred embodiments have been described, many modifications and variations are possible in light of the above teachings, and it is therefore understood that the invention can be practiced otherwise than as specifically described without departing from the scope of the appended claims.
Claims
1. a) at least one solid crystalline bio-based polyester polyol; b) at least one solid bio-based amorphous polyester polyol, and / or at least one liquid bio-based amorphous polyester; and c) at least one polyisocyanate; 1. A high bio-content polyurethane hot melt adhesive composition comprising at least one polyurethane prepolymer obtained from the reaction in the presence of a catalyst of A high bio-content polyurethane hot melt adhesive composition, wherein the adhesive composition comprises greater than 50 weight percent bio-based materials, based on the total weight of the adhesive composition.
2. The bio-based solid crystalline polyester polyol is derived from a reaction mixture comprising at least one polyacid or derivative thereof and at least one polyol, the derivative being preferably a carboxylic acid anhydride and / or ester of the polyacid; more preferably, the polyacid is a diacid, preferably selected from the group consisting of succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, dimer fatty acid, 2,5-furandicarboxylic acid, adipic acid and combinations thereof, and / or the polyol is a diol, preferably selected from the group consisting of ethylene glycol, diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, isosorbide and combinations thereof; most preferably, the bio-based solid crystalline polyester polyol is derived from a reaction mixture comprising sebacic acid and ethylene glycol.
10. The high bio-content polyurethane hot melt adhesive composition of claim 1.
3. The bio-based solid crystalline polyester polyol has a melting point of about 10 to about 110° C., preferably about 30 to about 90° C.; and / or a number average molecular weight of greater than about 1000 g / mol, preferably about 2000 to about 8000 g / mol.
3. The high bio-content polyurethane hot melt adhesive composition of claim 1 or 2.
4. The solid amorphous bio-based polyester polyol is derived from a reaction mixture comprising at least one polyol and at least one polyacid; preferably, the solid amorphous bio-based polyester polyol is derived from a reaction mixture comprising at least one hexitol anhydride and at least one multifunctional carboxylic acid; more preferably, the solid amorphous bio-based polyester polyol is derived from a reaction mixture comprising isosorbide and at least one multifunctional carboxylic acid selected from the group consisting of adipic acid, succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, furandicarboxylic acid, isophthalic acid, terephthalic acid, orthophthalic acid, dimerized fatty acid, trimerized fatty acid, and mixtures thereof; most preferably, the solid amorphous bio-based polyester polyol is derived from a reaction mixture comprising isosorbide, succinic acid, and dimer fatty acid. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 3.
5. The bio-based solid amorphous polyester polyol has a glass transition temperature (Tg) of about 5 to about 80° C., preferably about 10 to about 50° C.; and / or a number average molecular weight of greater than about 1000 g / mol, preferably about 1700 to about 5500 g / mol. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 4.
6. The bio-based liquid amorphous polyester polyol is derived from a reaction mixture comprising at least one polyol and at least one polyacid or derivative thereof, the derivative being preferably a carboxylic anhydride and / or ester of the polyacid; preferably, the polyol is selected from the group consisting of 1,2-propanediol, 1,3-butanediol (including R-, S- and racemic), 1,4-pentanediol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, dipropylene glycol, and polypropylene glycol or mixtures thereof, and / or the polyacid is selected from the group consisting of succinic acid, azelaic acid, sebacic acid, dodecanedioic acid, and dimerized fatty acid or mixtures thereof; more preferably, the bio-based liquid amorphous polyester polyol is derived from a reaction mixture comprising azelaic acid and diethylene glycol. The high bio-content polyurethane hot melt adhesive composition according to any one of claims 1 to 6.
7. The bio-based liquid amorphous polyester polyol has a glass transition temperature of less than about 0° C., preferably from about −75° C. to about −15° C., and / or a number average molecular weight of greater than about 1000 g / mol, preferably from about 1500 g / mol to about 5500 g / mol. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 6.
8. Further comprising at least one polyether polyol and / or at least one (meth)acrylic resin; The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 7.
9. the bio-based solid crystalline polyester polyol, the bio-based solid amorphous polyester polyol, and / or the bio-based liquid amorphous polyester polyol are partially or completely bio-based; and / or the composition further comprises at least one non-bio-based solid crystalline polyester polyol and / or at least one non-bio-based liquid amorphous polyester polyol. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 8.
10. The bio-based solid crystalline polyester polyol is present in an amount of about 10 to about 40 wt%, preferably about 15 to about 35 wt%, based on the total weight of the adhesive composition. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 9.
11. The total content of the solid bio-based amorphous polyester polyol and / or the liquid bio-based amorphous polyester polyol is about 15 to about 70% by weight, preferably about 20 to about 50% by weight, based on the total weight of the adhesive composition; The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 10.
12. Polyisocyanates include 4,4-diphenylmethane diisocyanate (MDI), hydrogenated MDI (H12MDI), partially hydrogenated MDI (H6MDI), xylylene diisocyanate (XDI), tetramethylxylylene diisocyanate (TMXDI), 4,4-diphenyldimethylmethane diisocyanate, dialkylene diphenylmethane diisocyanate, tetraalkylene diphenylmethane diisocyanate, 4,4-dibenzyl diisocyanate, isocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, isomers of toluylene diisocyanate (TDI), 1-methyl-2,4-diisocyanatocyclohexane, 1,6-diisocyanato-2,2,4-trimethylhexane, 1,6-diisocyanato-2,4,4-trimethylhexane, 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), tetramethylisocyanato xybutane-1,4-diisocyanate, naphthalene-1,5-diisocyanate (NDI), butane-1,4-diisocyanate, hexane-1,6-diisocyanate (HDI), dicyclohexylmethane diisocyanate, 2,2,4-trimethylhexane-2,3,3-trimethylhexamethylene diisocyanate, cyclohexane-1,4-diisocyanate, ethylene diisocyanate, methylenetriphenyl triisocyanate diisocyanate (MIT), phthalic acid bisisocyanatoethyl ester, trimethylhexamethylene diisocyanate, 1,4-diisocyanatobutane, 1,12-diisocyanatododecane, and dimer fatty acid diisocyanate, lysine ester diisocyanate, 4,4-dicyclohexylmethane diisocyanate, 1,3-cyclohexane or 1,4-cyclohexane diisocyanate, and combinations thereof; The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 11.
13. The catalyst may be a strongly basic amide, triethylamine, tributylamine, dimethylbenzylamine, N-ethylhexylmorpholine, N-methylhexylmorpholine, N-cyclohexylmorpholine, dimethylcyclohexylamine, dimorpholinodiethyl ether, 2-(dimethylaminoethoxy)-ethanol, 1,4-diazabicyclo[2,2,2]octane, 1-azabicyclo[3,3,0]octane, N,N,N',N'-tetramethylethylenediamine, selected from the group consisting of amines, N,N,N',N'-tetramethylbutanediamine, N,N,N',N'-tetramethylhexane-1,6-diamine, pentamethyldiethylenetriamine, tetramethyldiaminoethyl ether, bis-(dimethylaminopropyl)-urea, N,N'-dimethylpiperazine, 1,2-dimethylimidazole, di-(4-N,N-dimethylaminocyclohexyl)methane, organometallic compounds, and combinations thereof; The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 12.
14. The polyisocyanate is present in an amount of about 10 to about 25 weight percent, preferably about 15 to about 22 weight percent, based on the total weight of the adhesive composition. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 13.
15. The catalyst is present in an amount of about 0.05 to about 1 weight percent, preferably about 0.1 to about 0.5 weight percent, based on the total weight of the adhesive composition. The high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 14.
16. (i) adding all of the polyester polyol and optionally the (meth)acrylic resin, melting them, and mixing until homogeneous and free of moisture; (ii) adding at least one polyisocyanate and mixing the resulting mixture under vacuum at 80° C. to 120° C. until the reaction is complete; and (iii) adding catalyst and optional additives and stirring the mixture at 80° C. to 120° C. until homogenous. A method for producing the high bio-content polyurethane hot melt adhesive composition of any one of claims 1 to 15, comprising:
17. An electronic device, preferably a handheld device assembly, obtained with the high bio-content polyurethane hot melt adhesive composition according to any one of claims 1 to 15.
18. Use of the high bio-content polyurethane hot melt adhesive composition according to any one of claims 1 to 15 in manufacturing electronic devices, preferably handheld device assemblies.
Citation Information
Patent Citations
Bio-Based Reactive Polyurethane Hotmelt Adhesives
US20210163801A1